2014
DOI: 10.1016/j.cognition.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distance effects on incremental semantic interpretation of abstract sentences: Evidence from eye tracking

Abstract: a b s t r a c tA large body of evidence has shown that visual context information can rapidly modulate language comprehension for concrete sentences and when it is mediated by a referential or a lexical-semantic link. What has not yet been examined is whether visual context can also modulate comprehension of abstract sentences incrementally when it is neither referenced by, nor lexically associated with, the sentence. Three eye-tracking reading experiments examined the effects of spatial distance between words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 58 publications
4
42
1
Order By: Relevance
“…Recently, based on a large-scale (N = 334) study, Nieuwland and colleagues (2019) found that part of the late positivity effect of predictability may be explained in terms of semantic similarity. In addition, there is the possibility that semantic similarity effects are more likely to occur for words that appear close together (here, sentence context, album-pictures) than for distant relationships (discourse context, given that memory trace decreases with longer distance) (Guerra & Knoeferle, 2014). Therefore, we should not exclude the possibility that the positivity effect of predictability that we observed in the sentence condition is at least in part due to a semantic similarity effect.…”
Section: Effect Of Contextmentioning
confidence: 92%
“…Recently, based on a large-scale (N = 334) study, Nieuwland and colleagues (2019) found that part of the late positivity effect of predictability may be explained in terms of semantic similarity. In addition, there is the possibility that semantic similarity effects are more likely to occur for words that appear close together (here, sentence context, album-pictures) than for distant relationships (discourse context, given that memory trace decreases with longer distance) (Guerra & Knoeferle, 2014). Therefore, we should not exclude the possibility that the positivity effect of predictability that we observed in the sentence condition is at least in part due to a semantic similarity effect.…”
Section: Effect Of Contextmentioning
confidence: 92%
“…However, one might argue that cues in context differ at least sometimes in their appearance, timing, and relation to language and that we must derive a principled account of what languageworld relation elicits what effect on language comprehension (its time course and representations). To the extent that world-language relations govern context effects, the prediction from these findings is that verb-mediated action effects should influence comprehension and recall of the interpretation content more than cues that are not referentially tied into the interpretation [e.g., speaker gaze, relations between the queen was in agnoy and a depiction of the queen, emotional facial expressions cued by adjectives such as happy, distance between objects related to semantic similarity (Guerra and Knoeferle 2014)]. add evidence to the argument of distinct language-world relations modulating context effects: As participants in their studies listened to sentences such as Toby arrested the thief., they inspected both a picture of a thief and of a policeman to a similar extent and more than distractor objects during arrested the.…”
Section: Variation In Expectation-based Comprehension and In Context mentioning
confidence: 99%
“…Note that we are not claiming that these accounts, models or theories could not be adapted to include social context. We have selected one account (see Guerra and Knoeferle, 2014 , 2017 ; Knoeferle et al, 2014 on how the CIA can accommodate context effects in written language comprehension; see Knoeferle and Crocker, 2006 , 2007 for context effects in spoken language comprehension) to illustrate how enrichment with socially relevant information might be achieved.…”
Section: Extant Approaches To Social Effects In Language Processingmentioning
confidence: 99%
“…The outcome of this reconciliation is tracked (match vs. mismatch) via indices to ant and int, and a truth value tracks the veracity of manual responses. Regarding int i′ , reconciliation involves coindexing representations of (minimally) nouns/verbs with those of depicted objects/actions (see Guerra and Knoeferle, 2014 , 2017 on non-referential co-indexing). Additionally, revision of the sentence interpretation can be informed by the scene.…”
Section: The Social Coordinated Interplay Accountmentioning
confidence: 99%
See 1 more Smart Citation